ANALISA DAMPAK KONVERGENSI IFRS KE DALAM PSAK 13, 16, DAN 30 TERHADAP AKTIVITAS PERDAGANGAN SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arya Maulana; Murniati Mukhlisin (Institute for Research and Community Empowerment (LPPM TAZKIA), 2011)
The application of PSAK has been revised in reference with the IAS in the convergence of IFRS perspective. The objective of the research is to elaborate influence of this application on Trading Volume Activity (TVA) companies that implement it. This research uses quantitative method that focus to a single incident within a certain period of publication an annual financial statements of 56 companies who implemented PSAK 13, 16, and 30 revised in 2007. This study indicates that the publication of financial statements has not give a significant influence on the TVA despite there is an increase in trading activity at the time after publication.JEL Classification : M 41, L51Keywords : IAS, PSAK, Financial Statement Publication, Trading Volume Activity